Chemical engineering thermodynamics : an introduction to thermodynamics for undergraduate engineering students - Winnick, J. 1937- (John Wiley and Sons, 1997)
This book is about: basic principles; The energy balance; Thermodynamic properties; Poperty Interrelations.